On Accurate Strong Non-Split Domination in Graphs - A. Mohamed Ismayil; H. Sabitha Begum (Utilitas Mathematica, 2025)
Accurate strong non-split dominating set in a graph with the relevant illustration is described in this manuscript. Minimal accurate strong non-split dominating set and accurate strong non-split domination numbers are specified for graphs. For some popular graphs, bounds on accurate strong non-split domination numbers are determined. Strong non-split domination number connections with other well-known domi-nating parameters are discovered. A few theorem relating to accurate strong non-split domination numbers are presented and obtained.